2018
DOI: 10.1111/ases.12467
|View full text |Cite
|
Sign up to set email alerts
|

Conventional laparoscopic appendectomy versus double‐incision, three‐port laparoscopic appendectomy: A 1‐year randomized controlled trial

Abstract: DILA can be performed with operative outcomes that are equivalent to CLA but with superior cosmetic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…12 Prior to SILS, Double-incision laparoscopic appendectomy (DILA) was introduced as a means of further minimizing the invasiveness of traditional laparoscopic surgery, by decreasing then number of incisions. 13 A randomized control trial has demonstrated that DILA can be performed with equivalent operative outcomes with superior cosmetic outcomes. 13 Successful operations using DILA urged the push for SILS, as stated previously, primarily for cosmetic reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Prior to SILS, Double-incision laparoscopic appendectomy (DILA) was introduced as a means of further minimizing the invasiveness of traditional laparoscopic surgery, by decreasing then number of incisions. 13 A randomized control trial has demonstrated that DILA can be performed with equivalent operative outcomes with superior cosmetic outcomes. 13 Successful operations using DILA urged the push for SILS, as stated previously, primarily for cosmetic reasons.…”
Section: Discussionmentioning
confidence: 99%
“…13 A randomized control trial has demonstrated that DILA can be performed with equivalent operative outcomes with superior cosmetic outcomes. 13 Successful operations using DILA urged the push for SILS, as stated previously, primarily for cosmetic reasons. 11 In direct comparison to traditional laparoscopic appendectomy, SILS appendectomy can be conducted with comparable operative times, lengths of stay, and procedural complications, and with superior cosmetic outcomes -the main downside noted being the cost.…”
Section: Discussionmentioning
confidence: 99%
“…Jinhong Geng 1* , Jinfeng Yuan 2* , Xiangdong Kong 1 , Ming Wu 1 , Linwen Zeng 1 , Yuhong Hu 3 , and Jianming Gong 1 Brief Report Laparoscopic appendectomy (LA) traditionally uses 3 ports: 2 for the videoscope and 3 for the procedure. 1 More recently a large single port technique groups the 3 ports in a single site that uses a larger incision. 2 As an alternative to the 3-port and single-port methods, we developed a laparoscopic traction device to pull the appendix to facilitate its removal.…”
Section: Laparoscopic Traction Device For Assistance Of 2-port Laparoscopic Appendectomymentioning
confidence: 99%
“…Using an endoloop to tie off the appendix stump has been shown to be safe, and thus the use of a 10-mm port for the stapler can be avoided [5]. Various techniques to reduce the number [6, 7] and size of ports during LA have been published, and in children mini-instruments are commonly used [8, 9]. In adults use of a suture to suspend the appendix has been suggested by Roberts et al [7].…”
Section: Introductionmentioning
confidence: 99%